Humanin protects against chemotherapy‐induced stage‐specific male germ cell apoptosis in rats1. (16th April 2015) - Surampudi, P.; Chang, I.; Lue, Y.; Doumit, T.; Jia, Y.; Atienza, V.; Liu, P. Y.; Swerdloff, R. S.; Wang, C.
Summary: Humanin (HN) has cytoprotective action on male germ cells after testicular stress induced by heat and hormonal deprivation. To examine whether HN has protective effects on chemotherapy‐induced male germ cell apoptosis, we treated four groups of adult rats with (i) vehicle (control), (ii) HN, (iii) cyclophosphamide (CP); or (iv) HN+CP. To investigate whether the protective effects of HN on germ cells require the presence of Leydig cells, another four groups of rats were pre‐treated with ethane dimethanesulfonate (EDS), a Leydig cell toxicant, to eliminate Leydig cells. After 3 days, when Leydig cells were depleted by EDS, we administered: (i) vehicle, (ii) HN, (iii) CP; or (iv) HN+CP to rats. All rats were killed 12 h after the injection of HN and/or CP. Germ cell apoptosis was detected by TUNEL assay and quantified by numerical count. Compared with control and HN (alone), CP significantly increased germ cell apoptosis; HN +CP significantly reduced CP‐induced apoptosis at early (I–VI) and late stages (IX–XIV) but not at middle stages (VII–VIII) of the seminiferous epithelial cycle. Pre‐treatment with EDS markedly suppressed serum and intratesticular testosterone (T) levels, and significantly increased germ cell apoptosis at the middle (VII–VIII) stages. CP did not further increase germ cell apoptosis in the EDS‐pre‐treated rats. HN significantly attenuated germ cell apoptosis at the middle stages in EDS pre‐treated rats. To investigate whether HN has any direct effects on Leydig cell function, adult Leydig cells were isolated and treated with ketoconazole (KTZ) to block testosterone synthesis. HN was not effective in preventing the reduction of T production by KTZ in vitro. We conclude that HN decreases CP and/or EDS‐induced germ cell apoptosis in a stage‐specific fashion. HN acts directly on germ cells to protect against EDS‐induced apoptosis in the absence of Leydig cells and intratesticular testosterone levels are very low.